Analisis Penyebab Penurunan Kinerja Intercooler pada Mesin Induk KM Bintan Utama - Fathul Bari; Daryanto Daryanto; Rodlitul Awwalin (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the factors that cause the decline in intercooler performance on the main engine of KM Bintan Utama, its impact on engine performance, and the corrective measures that need to be taken. Based on the analysis, three main factors contribute to the decrease in intercooler performance: dirty air fins in the intercooler, lack of routine maintenance, and blockage in the seawater pipe filter. This decline in intercooler performance significantly affects the main engine, such as increased engine temperature, which can lead to damage to critical components. To address this issue, several actions need to be taken, including cleaning the intercooler air fins regularly and ensuring maintenance is carried out according to the recommended manual. Proper maintenance implementation will help maintain the performance of the main engine and extend the life of the intercooler and other components.